Design and Simulation of Chassis for Electric Cultivator - Dwi Santoso; Abdul Waris; Saat Egra (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Building or designing an electric cultivator requires a comprehensive study by paying attention to each main component, namely the chassis. The chassis serves as a place to attach the constituent components and holds the weight of the overall components contained in the tool. A good machine frame will increase the workability of the machine because the components that make up the cultivator are in the right layout. A good chassis design is needed to improve the performance of the electric cultivator. This study aims to design and simulate the strength analysis of the electric cultivator frame. This research consists of several stages, namely literature review, frame design, chassis strength simulation and chassis cultivator capability analysis. From the results of the analysis concluded that technically this tool is classified as safe with a loading condition of 18 kg and a support on its axis. However, it is still recommended that before production, the tool design must be re-optimized. Especially at the joints of the upper and lower frames near the pillow block. This is because this cross section is a critical area because it has a large equivalent stress value, has a small life cycle, and has a low safety factor. Keywords:   Design, Electric cultivator, Simulation